Peningkatan Usaha Kecil Industri Rumah Tangga Keripik Pisang di Kelurahan Kedungkandang - Ika Nuriyanti; Nisa'us Sholikah; Afifuddin (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
The problem faced by partners, namely the 'Bunda Sekarningsih' banana chip business, is the lack of production equipment and traditional production methods so that they have not implemented the principles of sanitation and hygienic food processing, as well as poor financial and administrative governance. The aim of implementing the program was to increase the production and income of IRT (Household Industry) partners in banana chips, as well as the knowledge and skills of producers in food processing and financial management. The method of implementing this program was counseling, training and assistance to the owner and employees of IRT banana chips 'Bunda Sekarningsih'. The results of the service program that has been carried out include: the availability of banana cutting tools that are designed and made by applying Higher Education Science and Technology so as to increase the quantity and quality of production; Increased knowledge and understanding of partners to apply sanitation principles and produce hygienic food; Increased knowledge and skills of partners to manage financial and managerial business with the POAC (Planning Organizing Actuating Controlling) concept.